1992
DOI: 10.1007/bf01973385
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal thymus development and impaired function of the immune system in rats after prenatal exposure to aciclovir

Abstract: Aciclovir (synonym: acyclovir) causes abnormal thymus development in rats. After treatment on day 10 of gestation a weight reduction of the organ is obvious in 21-day-old fetuses which persists postnatally. Adult male rats exposed in utero to one or three injections of 100 mg aciclovir/kg body wt given to the dam on day 10 of pregnancy showed a reduction of the thymus weight to 333 +/- 158 mg and 276 +/- 61 mg (control: 428 +/- 92 mg; n = 10). Corresponding alterations were detectable in female offspring. Live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 25 publications
1
2
0
1
Order By: Relevance
“…The low antibody titres in the chemical pesticide treated animals on all the days of the tests showed that both the IgM as well as IgG development is suppressed by chemical pesticides treatment even when pesticides are inoculated at subchronic and sublethal doses. Our findings agree with those of Stahlmann et al [5], who found a dose dependent decrease in IgG in rats exposed to acyclovir, and with Banerjee et al [6] who found that aldrin and DDT suppressed both IgG and IgM levels in the pesticide-exposed rats. However, our findings contrast with those of Founier et a/.…”
supporting
confidence: 93%
“…The low antibody titres in the chemical pesticide treated animals on all the days of the tests showed that both the IgM as well as IgG development is suppressed by chemical pesticides treatment even when pesticides are inoculated at subchronic and sublethal doses. Our findings agree with those of Stahlmann et al [5], who found a dose dependent decrease in IgG in rats exposed to acyclovir, and with Banerjee et al [6] who found that aldrin and DDT suppressed both IgG and IgM levels in the pesticide-exposed rats. However, our findings contrast with those of Founier et a/.…”
supporting
confidence: 93%
“…Examples of developmental immunotoxicity assessments with pharmaceutical compounds, including cyclosporine, dexamethasone, diazepam, aciclovir, and diethylstilbestrol (DES), have been described (Stahlmann et al, 1992;Schlumpf et al, 1989Schlumpf et al, , 1994Dietert et al, 2003;Fenaux et al, 2004;Hussain et al, 2005;Barrow et al, 2006;Luebke et al, 2006). Recently, it was suggested that the United States (US) Food and Drug Administration (FDA) has possibly observed a case of differential sensitivity where juvenile animals displayed effects not observed in toxicity studies conducted in the adult; however, due to confidentiality, no specific information could be shared.…”
Section: Review Articlementioning
confidence: 99%
“…In some offspring the thymus could no longer be detected [20]. Effects on T‐cell mediated responses were observed in a host resistance model in which the exposed offspring showed a decreased resistance to Trichinella spiralis (a highly T‐cell dependent defence model) [21]. In some cases acyclovir is prescribed to pregnant women.…”
Section: Developmental Immunotoxicitymentioning
confidence: 99%